A validation study of a modified Bouchard activity record that extends the concept of 'uptime' to Rett syndrome. (23rd June 2015) - Lor, Leon; Hill, Kylie; Jacoby, Peter; Leonard, Helen; Downs, Jenny
Abstract : Aim: The aim of this study was to investigate the validity of using a Bouchard activity record (BAR) in individuals with Rett syndrome to measure physical activity, as compared with pragmatic criterion standard measures of walking status and step counts recorded using the StepWatch activity monitor (SAM). Method: During the waking hours of 1 day, 43 females (mean age 21y, SD 9y) wore a SAM whilst a proxy completed a modified BAR. Responses to the BAR were compared among participants, who were grouped according to walking status, using the Mann–Whitney two‐sample rank‐sum test. Relationships were sought between BAR responses and step counts using linear regression. Results: According to the proxy‐reported BAR responses, those who needed assistance with walking spent more time sitting (median [interquartile range] 9h 15min [8h 8min–10h 30min] vs 6h 15min [4h 15min–8h 30min]; p <0.001) and less time standing (1h [38min–1h 30min] vs 2h 15min [45min–3h 45min]; p =0.04) than those who could walk independently. In those who could walk independently, time classified as 'uptime' (standing and walking) using the BAR was associated with increased step count ( r 2 =0.58; p <0.001). Interpretation: These data support the validity of proxy‐reported BAR responses. In those who could walk independently, uptime, classified using the BAR, could be used to estimate daily step count. This tool offers an inexpensive method for clinicians to gain insights into physical activity levels in individuals with Rett syndrome. What this paper adds: Data provides evidence for the validity of a proxy‐reported measure of physical activity in people with a neurodevelopmental disability. For those who walked independently, time classified as standing and walking (uptime) was strongly associated with step count over a 24‐hour period. For individuals with Rett syndrome, daily activity programmes aimed at increasing uptime could be an effective way of increasing daily step count. This article is commented on by Humphreys on pages1086–1087 of this issue.